Minimally invasive percutaneous nephrolithotomy versus endoscopic combined intrarenal surgery with flexible ureteroscope for partial staghorn calculi: A randomised controlled trial. (April 2016) - Wen, Jiaming; Xu, Gang; Du, Chuanjun; Wang, Bohan
Abstract: Background: To compare the efficacy and safety of simultaneous percutaneous nephrolithotomy combined with flexible ureteroscopic lithotripsy in Galdakao-Modified Supine Valdivia position (GMSV) with minimally invasive percutaneous nephrolithotomy (MPCNL) for partial staghorn calculi. Methods: 67 patients with partial staghorn calculi were randomly divided into two groups. In MPCNL Group, conventional MPCNL was performed in the prone position. In the other group, simultaneous combined MPCNL and flexible ureteroscopic lithotripsy (Endoscopic Combined Intra-Renal Surgery, ECIRS) serves as single session treatment in the GMSV position (ECIRS Group). Demographic, clinical characteristic, perioperative complications and stone free rate (SFR) were recorded. Results: No significant difference was detected between two groups concerning the age, body mass index, hydronephrosis, stone burden and location. The mean operative time was 105.33 ± 30.28 min in ECIRS group, which is longer (p = 0.002) than MPCNL group (83.58 ± 24.37 min). The one-step SFR was significantly higher (p = 0.007) in the ECIRS group compared to MPCNL group (87.88% vs 58.82%). The mean blood loss was 77.21 ± 41.21 ml for ECIRS group and 86.43 ± 35.61 ml for MPCNL group (p = 0.330). Overall, complication rate is low in both groups. No statistical difference was found in regards to the clinical complications between the two groups (p = 0.409). After the ancillary treatments, the final SFR was 96.97% in ECIRS group and 91.18% in MPCNL group (p = 0.628). Conclusion: Simultaneous combined MPCNL and flexible ureteroscopic lithotripsy is an effective and safe treatment for partial staghorn calculi, with significantly higher one-step SFR when compared to conventional MPCNL monotherapy, without additional procedure-related complications. Highlights: Endoscopic combined intra-renal surgery is a safe and effective treatment for partial staghorn calculi. The one-step stone-free rate for endoscopic combined intra-renal surgery is significantly higher compared to MPCNL. No additional procedure-related complication was observed for endoscopic combined intra-renal surgery.